Lanthanum cobaltite black pigments with perovskite structure - Melo, D.; Vieira, F. T G; Costa, T. C C; Soledade, L. E B; Paskocimas, C. A.; Melo, D. M A; Longo, Elson [UNESP]; Marinho, E. P.; Souza, A. G.; Santos, I. M G (Elsevier, 2013)
In this work La1-xCaxCoO3 (x = 0-0.4) pigments were synthesized by the polymeric precursor method with heat treatments at 700, 800 and 900 C for 4 h. The powders were characterized by colorimetry, UV-vis spectroscopy and powder X-ray diffraction (XRD). The X-ray diffraction patterns showed the presence of a single phase perovskite, changing its structure from rhombohedral to cubic, when calcium was added to the lattice. All of the pigments had a black colour with a strong absorption over the whole of the visible spectrum as a consequence of the different oxidation states of cobalt and the high short-range disorder. The substitution of Ca2+ for La3+ did not influence the pigment colour but decreased its final cost. © 2013 Elsevier Ltd. All rights reserved.
Keywords: Black pigment; Cobaltite; Lanthanum; Perovskite; Polymeric precursor method; Solid solution; Lanthanum cobaltite; Perovskite structures; Polymeric precursor methods; Powder X ray diffraction; Strong absorptions; UV-vis spectroscopy; Absorption spectroscopy; Calcium; Cobalt compounds; Color; Lanthanum alloys; Polymers; Solid solutions; Ultraviolet visible spectroscopy; X ray diffraction; X ray powder diffraction